Sisterhood everlasting : a novel - Brashares, Ann. (New York : Random House, 2011)
Despite having jobs and men that they love, Tibby, Lena, Carmen, and Bridget know something is missing: the closeness that once sustained them. Carmen is a successful actress in New York, engaged to be married, but misses her friends. Lena finds solace in her art, teaching in Rhode Island, but still thinks of Kostos and the road she didn't take. Bridget lives with her longtime boyfriend, Eric, in San Francisco, and though a part of her wants to settle down, a bigger part can't seem to shed her old restlessness. When Tibby sends the others plane tickets for a reunion they all breathlessly await, it will change their lives forever, but in ways none of them ever expected. The traveling pants are gone, but the sisterhood lasts forever.
English Language & Literature.
Keywords: Female friendship -- Fiction; Interpersonal relations -- Fiction; Life change events -- Fiction; Bildungsromans